2021
DOI: 10.1111/ijlh.13641
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency of the autoverification workflow for nucleated red blood cell reporting in the hematology laboratory

Abstract: Objective Although the microscopic manual count is considered the standard method for NRBC enumeration, modern hematology analyzers can perform this task automatically with reliable accuracy and efficiency. This study aims to evaluate the diagnostic performance of the Sysmex XN hematology analyzer and to construct the optimal workflow for accurate and efficient NRBC reporting. Methods Specimens containing different levels of NRBC were included. Analytical performance was evaluated via method comparison with fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…They are preferable to manual count by being cost effective and convenient. Previous studies in other countries have been conducted to determine the precision and diagnostic accuracy of Sysmex XN series and they have been very encouraging [2,12]. Our study also shows that Sysmex XN-1000 analyzer with its WNR channel is highly sensitive (90.56%) and specific (88.30%) in enumerating nRBCs.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…They are preferable to manual count by being cost effective and convenient. Previous studies in other countries have been conducted to determine the precision and diagnostic accuracy of Sysmex XN series and they have been very encouraging [2,12]. Our study also shows that Sysmex XN-1000 analyzer with its WNR channel is highly sensitive (90.56%) and specific (88.30%) in enumerating nRBCs.…”
Section: Discussionsupporting
confidence: 67%
“…In the positive samples, those with nRBCs identified on manual microscopy, Sysmex XN 1000 showed positive predictive value of 88.26%. It was slightly lower than other studies due to some false negative values [2]. And in negative samples it showed negative predictive value of 90.6%.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Automated analyzers have been introduced in hematology laboratories and blood bank laboratories; however, few studies have focused on laboratory efficiency in these laboratories with high manual workload [ 24 - 26 ]. These studies demonstrated the usefulness and applicability of FMEA in clinical laboratories and showed that automated methods are associated with lower RPNs than manual methods, which is in line with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleated red blood cells (NRBCs) are premature erythrocyte precursors rarely present in the circulatory systems of healthy adults [1,2]. They normally reside in the bone marrow of humans of all ages (Figure 1), where the common myeloid progenitor cell differentiates into more developed cells to finally become an erythroblast [3][4][5].…”
Section: Introductionmentioning
confidence: 99%